Small‐Molecule Prodrug Nanoassemblies: An Emerging Nanoplatform for Anticancer Drug Delivery. Issue 52 (3rd August 2021) - Li, Guanting; Sun, Bingjun; Li, Yaqiao; Luo, Cong; He, Zhonggui; Sun, Jin
Abstract: The antitumor efficiency and clinical translation of traditional nanomedicines is mainly restricted by low drug loading, complex preparation technology, and potential toxicity caused by the overused carrier materials. In recent decades, small‐molecule prodrug nanoassemblies (SMP‐NAs), which are formed by the self‐assembly of prodrugs themselves, have been widely investigated with distinct advantages of ultrahigh drug‐loading and negligible excipients‐trigged adverse reaction. Benefited from the simple preparation process, SMP‐NAs are widely used for chemotherapy, phototherapy, immunotherapy, and tumor diagnosis. In addition, combination therapy based on the accurate co‐delivery behavior of SMP‐NAs can effectively address the challenges of tumor heterogeneity and multidrug resistance. Recent trends in SMP‐NAs are outlined, and the corresponding self‐assembly mechanisms are discussed in detail. Besides, the smart stimuli‐responsive SMP‐NAs and the combination therapy based on SMP‐NAs are summarized, with special emphasis on the structure–function relationships. Finally, the outlooks and potential challenges of SMP‐NAs in cancer therapy are highlighted. Abstract : Recent trends in small‐molecule prodrug nanoassemblies (SMP‐NAs) are outlined, and the corresponding self‐assembly mechanisms are discussed in detail. Besides, the smart stimuli‐responsive SMP‐NAs and the combination therapy based on SMP‐NAs are summarized, with special emphasis on the structure–function relationships. Finally, the outlooks and potential challenges of SMP‐NAs in cancer therapy are highlighted.